2023
DOI: 10.1097/ajp.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Activity Pacing and Negative Emotions in Patients With Chronic Pain

David Attali,
Floriane Leguay,
Lola Milcent
et al.

Abstract: Objectives: Chronic pain is a major health problem given its high prevalence and its multiple consequences on the physical and psychological functioning of patients. It is therefore important to determine the relationship between these consequences and pain management strategies such as activity pacing. This review aimed to examine the association between activity pacing and the level of negative emotions in chronic pain. A second objective was to explore sex differences in this association. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(169 reference statements)
1
0
0
Order By: Relevance
“…This study found that pain is one of the key factors affecting exercise, consistent with previous studies (Borisovskaya et al, 2020). Pain not only directly affects exercise but also leads to negative emotions (self-denial) and reactions (negative coping), which indirectly affect patient movement (Attali et al, 2023). Therefore, in addition to disease treatment and pain control, the mental health of patients with chronic pain and kinesiophobia also needs special attention (Hemmati et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This study found that pain is one of the key factors affecting exercise, consistent with previous studies (Borisovskaya et al, 2020). Pain not only directly affects exercise but also leads to negative emotions (self-denial) and reactions (negative coping), which indirectly affect patient movement (Attali et al, 2023). Therefore, in addition to disease treatment and pain control, the mental health of patients with chronic pain and kinesiophobia also needs special attention (Hemmati et al, 2021).…”
Section: Discussionsupporting
confidence: 89%